Privatization of public enterprises in Nigeria: Valuation issues and problems - Tajudeen, Aluko Bioye (Journal of Business Economics and Management, 2004)
Privatization of public enterprises is a rapidly growing phenomenon in developing countries. However, it requires a lot of policy decisions and careful planning, which depend on high‐quality accounting and valuation data. But, the major controversy which trailed the first phase of privatization programmes in Nigeria is the asset valuation methodology. This article therefore examines valuation issues and problems besetting divestiture of public enterprises in the country and offers suggestions toward improving upon the quality of asset valuation for privatization.First Published Online: 14 Oct 2010